(untitled) (R&E-SOURCE, 2014)
The Internet as a global system of interconnected computer networks can be used as a new kind of learning environment. The majority of its educational and didactical potentials are hidden and not exploited when it is simply regarded as presentation or delivering tool for subject material. In my talk I will critically review some educational trends as well as their application in Math Education.